SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI USAHA KULINER DI DAERAH BAGAN BATU DENGAN MENGGUNAKAN METODE TOPSIS - Wahyudi Seto Wardana; Volvo Sihombing; Deci Irmayani (Politeknik Bisnis Indonesia, 2021)
This study aims to design a decision support system for choosing a culinary business location typical of the Bagansiapiapi area in the Bagan Batu area. The many variations of the typical culinary of Bagansiapiapi are in great demand by the people in the Bagan Batu area. Therefore, opening a culinary business for regional specialties is one of the businesses that has the potential to advance in Bagan Batu. To help entrepreneurs who want to choose a culinary business location in the Bagan Batu area, a computer-based Decision Support System is designed. The decision support system for selecting the location of this entrepreneur uses the Topsis method. The criteria used in this study consisted of 5 criteria, namely the level of population density, rental fees, access to business locations, convenience of parking lots, cleanliness of business locations. The results of this study are recommendations for business locations in the form of alternative rankings that can be taken into consideration as the chosen location. Of the 5 alternative data processed in this DSS, the best alternative location is location 4 with a weighted value of 0.6566.